DISAIN DAN PEMBUATAN PEMBANGKIT ALIRAN METODE ROLL WIPER UNTUK SISTEM PENGUKURAN KONSENTRASI PORFIRIN-Fe BERBASIS SENSOR GMR - Aminudin, Ahmad; Djamal, Mitra; Suprijadi, Suprijadi; Tjahyono, Daryono Hadi; R, Juniastel. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Has made generating fluid flow wiper roll method used in measurement systems Fe concentration of porphyrin-based GMR sensor. This measurement system requires a low flow and can be controlled. Generating low flow can be generated with a wiper roll method. Wiper roll method works based on circular sweeping using three roll bearings. Three bearings are used to suppress the elastic hose interchangeably. Shifting the emphasis bearing against the elastic hose causes the fluid flow. Three roll bearing load divided by the same angle is 120o with a radius of 30mm to the length of the shaft so as to produce the same trajectory. The test results showed that the speed of the motor has a sensitivity to the motor voltage for 4,75rpm / V, the velocity of fluid flow sensitivity to the motor voltage for 0,015mL / V and the motor starts to respond after the motor voltage is greater than 3 volts. Key Word : Flow Fluid Generator, Roll Wiper Method, sensitive.